Regulating cancer risk prediction: legal considerations and stakeholder perspectives on the Canadian context - Palmira Granados Moreno; Terese Knoppers; Ma’n H. Zawati; Michael Lang; Bartha M. Knoppers; Michael Wolfson; Hermann Nabi; Michel Dorval; Jacques Simard; Yann Joly (Human Genetics, 2023)
Risk prediction models hold great promise to reduce the impact of cancer in society through advanced warning of risk and improved preventative modalities. These models are evolving and becoming more complex, increasingly integrating genetic screening data and polygenic risk scores as well as calculating risk for multiple types of a disease. However, unclear regulatory compliance requirements applicable to these models raise significant legal uncertainty and new questions about the regulation of medical devices. This paper aims to address these novel regulatory questions by presenting an initial assessment of the legal status likely applicable to risk prediction models in Canada, using the CanRisk tool for breast and ovarian cancer as an exemplar. Legal analysis is supplemented with qualitative perspectives from expert stakeholders regarding the accessibility and compliance challenges of the Canadian regulatory framework. While the paper focuses on the Canadian context, it also refers to European and U.S. regulations in this domain to contrast them. Legal analysis and stakeholder perspectives highlight the need to clarify and update the Canadian regulatory framework for Software as a Medical Device as it applies to risk prediction models. Findings demonstrate how normative guidance perceived as convoluted, contradictory or overly burdensome can discourage innovation, compliance, and ultimately, implementation. This contribution aims to initiate discussion about a more optimal legal framework for risk prediction models as they continue to evolve and are increasingly integrated into landscape for public health.

A response to “Personalised medicine and population health: breast and ovarian cancer” - Antonis Antoniou; Hoda Anton-Culver; Alexander Borowsky; Mireille Broeders; Jennifer Brooks; Anna Chiarelli; Jocelyne Chiquette; Jack Cuzick; Suzette Delaloge; Peter Devilee; Michael Dorval; Douglas Easton; et al. (Human Genetics, 2019)

Do women change their breast cancer mammogram screening behaviour after BRCA1/2 testing? - Geneviève Larouche; Jocelyne Chiquette; Sylvie Pelletier; Jacques Simard; Michel Dorval (Familial Cancer, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

The knowledge value-chain of genetic counseling for breast cancer: an empirical assessment of prediction and communication processes - Nabil Amara; Jolyane Blouin-Bougie; Jalila Jbilou; Norrin Halilem; Jacques Simard; Réjean Landry (Familial Cancer, 2016)

miR-20a represses endothelial cell migration by targeting MKK3 and inhibiting p38 MAP kinase activation in response to VEGF - Anne-Laure Pin; François Houle; Maëva Guillonneau; Éric R. Paquet; Martin J. Simard; Jacques Huot (Angiogenesis, 2012)

Self-reported mammography use following BRCA1/2 genetic testing may be overestimated - Geneviève Larouche; Karine Bouchard; Jocelyne Chiquette; Christine Desbiens; Jacques Simard; Michel Dorval (Familial Cancer, 2012)

From polar night to midnight sun: photoperiod, seal predation, and the diel vertical migrations of polar cod (Boreogadus saida) under landfast ice in the Arctic Ocean - Delphine Benoit; Yvan Simard; Jacques Gagné; Maxime Geoffroy; Louis Fortier (Polar Biology, 2010)

Partnering in Oncogenetic Research – The INHERIT BRCAs Experience: Opportunities and Challenges - Denise Avard; Peter Bridge; Lucie M. Bucci; Jocelyne Chiquette; Michel Dorval; Francine Durocher; Doug Easton; Béatrice Godard; David Goldgar; Bartha Maria Knoppers; Rachel Laframboise; Bernard Lespérance; et al. (Familial Cancer, 2006)

Molecular and genealogical characterization of the R1443X BRCA1 mutation in high-risk French-Canadian breast/ovarian cancer families - Hélène Vézina; Francine Durocher; Martine Dumont; Louis Houde; Csilla Szabo; Martine Tranchant; Jocelyne Chiquette; Marie Plante; Rachel Laframboise; Jean Lépine; Heli Nevanlinna; Dominique Stoppa-Lyonnet; et al. (Human Genetics, 2005)

Study of the drug-drug interaction between simvastatin and cisapride in man - Chantale Simard; Gilles E. O'Hara; Jacques Prévost; Rudolf Guilbaud; Robert Massé; Jacques Turgeon (European Journal of Clinical Pharmacology, 2001)